Pelatihan Kewirausahaan "Pemberdayaan PKK Bibis Luhur RW 22 Sebagai PKK yang Siap Berbisnis" - Dian Indriana Hapsari; Sugiarti Sugiarti; Sugiyarmasto Sugiyarmasto; Yustinus Joko D. N.; Endang Widyastuti (Journal of Health (JoH), 2017)
Entrepreneurship has a lot of sense, according to Thomas W. Zimmerer, entrepreneurship is the application of new innovation and creativity for solving problems and take advantage of the opportunities that a person faces every day. The purpose of this “Pengabdian Masyarakat” is to provide training and knowledge of entrepreneurship to the PKK in RW 22 Nusukan to be able to independently and develop the region as a center of RW 22 Nusukan home industry pastries in Surakarta. The conclusion of the implementation activities of the Entrepreneurship Training "Empowerment PKK RW 22 Nusukan As the PKK is ready to Business" carried out smoothly. In addition, participants are also expected to understand the importance of entrepreneurship to improve the economy in an increasingly difficult economic.